A queuing-based mathematical model for the congested network design problem under demand uncertainty. (16th December 2019) - Shojaie, Amir Abbas; Kaviani, Mohamad Amin
In this study, we propose a queuing-based mathematical model for analysing the congestion phenomenon in a transportation network. For this purpose, we present a mathematical model for network design with the objective of the cost minimisation and optimal demand satisfaction under demand uncertainty situation. The queuing theory usage helps to better model the congestion item caused by customers' referrals to the facilities of the transportation network. Moreover, a numerical example is solved to demonstrate the validity of the proposed model. To the best of the authors' knowledge, this is the first study which looks at the congested transportation network problem considering demand uncertainty from a queuing theory perspective.